Peningkatan Hasil Belajar Fisika Melalui Pendekatan Konstruktivisme dengan Metode Siklus Belajar Karplus di MAN 2 Cirebon - Imas Salamah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to determine the improvement of physics learning outcomes through a constructivism approach with the Karplus cycle learn method. This research is an action research, conducted in two cycles including planning, implementation, observation, and reflection activities. The subject of the study was a student of class XI MIA 2 MAN 2 Cirebon city. The results showed that the average score of learning outcomes in cycle I of 37.83% increased to 94.59% in cycle II. Based on the assessment of the results of affective and psychomotor observations, there was an increase from cycle I to cycle II. The results of affective observations in cycle 1 of 54.18% increased to 81.26% in cycle II. The results of psychomotor observations in cycle I of 65.16% increased to 74.47% in cycle II. The implementation of learning by applying a constructivism approach with the karplus cycle learn method can improve physics learning outcomes in class XI MIA 2 MAN Cirebon city.